Herbicide Application Best Management Practices for Citrus Grove Workers - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack W. Hebb; P. Chris Wilson; Geovanne Stinghen (EDIS)
Revised! AE246, a 13-page illustrated fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, Chris Wilson, and Geovanne Stinghen, is part of the Best Management Practices (BMPs) for Citrus Grove Workers series. It covers personal protective equipment, tractor and herbicide preventive maintenance, mixing and loading, posting, herbicide application and spill containment. Includes quizzes and references. Published by the UF Department of Agricultural and Biological Engineering, March 2009.